Facile synthesis, electrical and optical properties of Cu-doped GaN nanorods by sol-gel technique - Aydin, Cihat; Khusayfan, Najla M.; Al-Ghamdi, Ahmed A.; El-Tantawy, Farid; Farooq, W. A.; Yakuphanoğlu, Fahrettin (Springer, 2016)
Here, we report, for the first time, synthesis of Cu-doped GaN nanorods by a simple sol-gel approach in the absence of any catalyst. The morphology of the as-synthesized Cu-doped GaN nanorods was examined in terms of X-ray diffraction, field emission scanning electron microscopy, high-resolution scanning electron microscopy and energy-dispersive X-ray spectroscopy. Detailed structural studies indicated that the synthesized products are hexagonal wurtzite GaN nanorods with large scale and high purity. The nanorods have diameters in the range of 30-50 nm and length of a few tens of micrometers. To assess the properties of the transparent conducting films, the electrical conductivity of as-prepared green GaN and Cu-doped GaN was studied. Finally, the influence of Cu content on the optical properties of GaN has been investigated. The Cu-doped GaN nanorods could be the basis for building integrated nanoscale magneto-electronic devices.
Keywords: GaN nanorods; Sol-gel method; Electrical and optical properties